Selected Ophthalmological Features in Children with Septo-Optic Dysplasia and Optic Nerve Hypoplasia. (2nd November 2022) - Salman, Michael S.; Hossain, Shakhawat; Carson, Elizabeth; Ruth, Chelsea A.; Clark, Ian H.
ABSTRACT: Septo-optic dysplasia (SOD) and optic nerve hypoplasia (ONH) cause congenital visual impairment. Their aetiology is mostly unknown. Our aim was to investigate the prevalence of selected ophthalmological features in patients with these disorders. A chart review was performed on patients with SOD/ONH. Ophthalmological data were extracted. There were 102 patients (56 males). The median age at the end of the study was 12.7 years. Best-corrected visual acuity ranged from normal to no light perception. Bilateral ONH was more common than unilateral ONH. Strabismus (85%) and to a lesser extent nystagmus (52%) were both very common in our cohort. Patients with esotropia had worse visual acuity than those who had exotropia. The presence of nystagmus was more likely in cases with bilateral ONH. Therefore, patients with SOD/ONH may have normal visual acuity. Many have strabismus, which may cause amblyopia thereby further decreasing visual acuity. Nystagmus occurs commonly and its presence typically indicates bilateral ONH.